The Impact of Motivating Tariffs and Competition on Electric Power Market in OECD Country-Members - A. V. Podlesnaya (Вестник Российского экономического университета имени Г. В. Плеханова)
The positive impact of motivating tariffs on the development of renewable energy sources (RES) was confirmed by numerous empiric research. Similar impact of competition on electric power market has not been adequately studied. Current research shows the influence of competition on electric power market not only on the development of generation based on RES, but on the development of technologies of RES-generation and efficiency of relative mechanisms of state support. At the same time it should be mentioned that findings of research are not dubious.  By analyzing literature the author formulated a hypothesis about growing impact of motivating tariffs on RES development with higher competition on electric power market. To verify the hypothesis the author used information about an increase in capacity of wind and solar power stations (WPS and SPS) per capita of the population in OECD country-members in 2000–2018 as key drivers of RES development in the region. Findings of the research show that in OECD country-members with higher competition on electric power market the impact of motivating tariffs on the growth in WPS and SPS capacity was much higher.